Mapping combined wildfire and heat stress hazards to improve evidence-based decision making. (June 2019) - Vitolo, Claudia; Di Napoli, Claudia; Di Giuseppe, Francesca; Cloke, Hannah L.; Pappenberger, Florian
Abstract: Heat stress and forest fires are often considered highly correlated hazards as extreme temperatures play a key role in both occurrences. This commonality can influence how civil protection and local responders deploy resources on the ground and could lead to an underestimation of potential impacts, as people could be less resilient when exposed to multiple hazards. In this work, we provide a simple methodology to identify areas prone to concurrent hazards, exemplified with, but not limited to, heat stress and fire danger. We use the combined heat and forest fire event that affected Europe in June 2017 to demonstrate that the methodology can be used for analysing past events as well as making predictions, by using reanalysis and medium-range weather forecasts, respectively. We present new spatial layers that map the combined danger and make suggestions on how these could be used in the context of a Multi-Hazard Early Warning System. These products could be particularly valuable in disaster risk reduction and emergency response management, particularly for civil protection, humanitarian agencies and other first responders whose role is to identify priorities during pre-interventions and emergencies. Highlights: Overestimating the correlation between heat stress and forest fires danger could lead to underestimating potential impact. A simple methodology to map areas prone to concurrent hazards, using layers designed for Multi-Hazard Early Warning Systems. These layers could be particularly valuable in disaster risk reduction and emergency response management.